Odpowiedzi

2010-03-08T16:18:25+01:00
A)

-3x = 2x - 10
-2x -3x = -10
-5x = -10 / : (-5)
x = 2

b)

2x - 2 = 7 - x
2x + x = 7 + 2
3x = 9 / : 3
x = 3

c)

10 = 4 - 2x
2x = 4 - 10
2x = -6 / : 2
x = -3

d)

-(2x - 1) = 4
-2x + 1 = 4
-2x = 4-1
-2x = 3 / : (-2)
x = 3/2
x = 1,5

e)

2(x+1) = x
2x + 2 = x
x = -2

f)

2t - (3t+1) = 6
2t - 3t -1 = 6
-t = 6+1
-t = 7 / : (-1)
t = -7

g)

-(4 + x) = 2(3-x)
-4 - x = 6 - 2x
x = 6 + 4
x = 10

h)

3(y+6) - y = 2(y + 9)
3y + 18 - y = 2y + 18
3y - y - 2y = 18-18
0=0

i)

(x-7) - 2(3x+5) = 3
x-7 - 6x + 10 = 3
x-6x = 3+7-10
-5x = 0 / : (-5)
x = 0
Najlepsza Odpowiedź!
2010-03-08T16:25:51+01:00
A)
-3x = 2x - 10
-3x-2x = - 10
-5x = - 10 / :(-5)
x = 2

b)
2x - 2 = 7 - x
2x + x = 7 + 2
3x = 9 /:3
x = 3


c)
10 = 4 - 2x
2x = 4 - 10
2x = -6 /:2
x = - 3


d)
- (2x - 1) = 4
- 2x + 1 = 4
- 2x = 4 - 1
- 2x = 3 / (-2)
x = - 1,5


e)
2 (x + 1) = x
2x + 2 = x
2x - x = - 2
x = -2


f)
2t - (3t + 1) = 6
2t - 3t - 1 = 6
2t - 3t = 6+1
-t = 7 /(-1)
t = -7


g)
-(4 + x) = 2(3 - x)
-4 - x = 6 - 2x
-x + 2x = 6 + 4
x = 10


h)
3(y+6) - y = 2(y + 9)
3y + 18 - y = 2y + 18
3y - y - 2y = 18 - 18
0 = 0

i)
(x - 7) - 2(3x + 5) = 3
x - 7 - 6x - 10 = 3
x - 6x = 3+ 7 + 10
- 5x = 20 / : (-5)
x = -4
2010-03-08T16:25:51+01:00
A) -3x = 2x - 10
- 3x - 2x = 10
- 5x = 10 / :(-5)
x = -2

b) 2x - 2= 7 - x
2x + x = 7 + 2
3x = 9 / : 3
x = 3

c) 10 = 4 - 2x
10 - 4 = -2x
6 = -2x / :(-2)
-3 = x

d) - (2x - 1) = 4
- 2x + 1 = 4
- 2x = 4-1
- 2x = 3 / :(-2)
x = -1,5

e) 2( x + 1) = x
2x + 3 = x
2x - x = -3
x = -3

f) 2t-(3t + 1) = 6
-6t + 2t = 6
- 4t = 6 / :(-4)
t = -1,5

g) - (4 + x) = 2 (3 - x)
-4 -x = 6 - 2x
-x + 2x = 6 + 4
x = 10

h) 3(y+6) - y = 2 (y + 9)
3y + 18 -y = 2y + 18
3y - y - 2y = 18 -18
0 = 0

i) ( x-7)-2(3x +5) = 3
(x-7) - 6x - 10 = 3
x- 6x = 3+7+10
-5x = 20 /:(-5)
x = -4